1997
DOI: 10.1161/01.atv.17.2.383
|View full text |Cite
|
Sign up to set email alerts
|

Remodeling and Shuttling

Abstract: In normal physiology, cells are exposed to cholesterol acceptors of different sizes simultaneously. The current study examined the possible interactions between two different classes of acceptors, one large (large unilamellar phospholipid vesicles, LUVs) and one small (HDL or other small acceptors), added separately or in combination to Fu5AH rat hepatoma cells. During a 24-hour incubation, LUVs of palmitoyl-oleoyl phosphatidylcholine at 1 mg phospholipid (PL) per milliliter extracted ≈20% of cellular unesteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
18
0

Year Published

1997
1997
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 49 publications
(20 citation statements)
references
References 62 publications
2
18
0
Order By: Relevance
“…Approximately 20-nm-diameter SUV were prepared by sonication (24), and 100-or 200-nm-diameter LUV were prepared by extrusion through polycarbonate filters (25). Enthalpies of apo A-I binding to unilamellar egg PC vesicles were measured by isothermal titration calorimetry as described (20,24).…”
Section: Methodsmentioning
confidence: 99%
“…Approximately 20-nm-diameter SUV were prepared by sonication (24), and 100-or 200-nm-diameter LUV were prepared by extrusion through polycarbonate filters (25). Enthalpies of apo A-I binding to unilamellar egg PC vesicles were measured by isothermal titration calorimetry as described (20,24).…”
Section: Methodsmentioning
confidence: 99%
“…Plasma membrane cholesterol depletion was accomplished by pretreatment of cultured cells with ␤-cyclodextrin (10 M), which removes unesterified cholesterol from the cell membrane (19) for 30 min at 37°C immediately followed by chilling the cells to 4°C.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, small unilamellar vesicles could be substituted for the LUV. These effects are not specific to macrophages because in studies with Fu5AH hepatoma cells, HDL particles or cyclodextrin were found to be able to shuttle cell cholesterol to LUV (29). mulate cholesterol in both the free and ester pools.…”
Section: Influence Of 2oh ␤ CD Concentration On Cholesterol Effluxmentioning
confidence: 99%